THE DYNAMICS OF PHYSICAL ACTIVITY OF STUDENTS OF SENIOR CLASSES DURING DISTANCE EDUCATION IN THE CONDITIONS OF THE MILITARY STATE - Тонкопей, Юлія (SWorldJournal, 2024)
The paper examines issues related to schoolchildren’s adaptation to learning in martial law under the influence of systematic events of a stressful nature. Distance learning in the context of the war led to a decrease in the volume and quality of physical